The Relationship Between Self-Control and Conformity on Consumptive Behavior in Fashion Product Purchases Using Pay Later Payment Method Among Students in Yogyakarta - Masri, Nur Ilmia; Warastri, Annisa (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Consumptive behavior in purchasing fashion products through paylater services is increasing among students in Yogyakarta and has the potential to cause financial problems, especially for individuals with low self-control and a tendency to follow peer pressure. Good self-control allows individuals to regulate their shopping impulses, while conformity can encourage students to conform to trends and lifestyles of their peers. This study aims to determine the relationship between self-control and conformity with consumptive behavior in purchasing fashion products with the paylater payment method for students in Yogyakarta. The research method uses a correlational quantitative approach with a sample of 100 students selected through purposive sampling techniques. The instruments used include the self-control scale, the conformity scale, and the consumptive behavior scale. The results of the study show that there is a significant relationship between self-control and consumptive behavior as well as between conformity and consumptive behavior. The lower the student's self-control, the higher the consumptive behavior, and the higher the tendency to conform, the greater the opportunity for students to make consumptive purchases. Simultaneously, both variables were proven to have a significant effect on the consumptive behavior of students using PayLater. This study concludes that self-control and conformity are important factors in shaping consumptive behavior, so it is necessary to increase financial literacy and self-regulation so that students are wiser in using PayLater services.